COMPARATIVE ANALYSIS OF OCCLUSIVE DRESSING AND OPEN WOUND TREATMENT IN PREVENTION OF SURGICAL SITE INFECTIONS - Srivastava, Arvind; Solanki, Prakshi (International Journal of Research -GRANTHAALAYAH, 2019)
Surgical site infections (SSIs) are defined as infections of the tissues, organs, or spaces exposed by surgeons during performance of an invasive procedure. Motivation/Background: A lot of expense both with regards to nursing time and dressing material costs is invested in prevention of SSI using occlusive surgical incision site dressing. But to what extent is this beneficial over open wound treatment? In the present study, we have compared the incidence of SSIs in surgical wounds treated with occlusive dressings versus those treated with open wound treatment to find out the same. Method: The study was conducted on 860 patients of General Surgery wards. Patients were categorized under two groups of cases where (1) Dressing was opened after 24 hours and then only open wound treatment by cleaning with Betadine 12 hourly was done till stitch removal and (2) Dressing was opened after 48 hours and then again after every 2 days occlusive dressing was done until stitch removal. Result: A Chi-Square Test was performed to understand if Occlusive dressings have an added advantage over Open Wound Treatment in prevention of SSIs. Conclusion: Occlusive Dressings have no added advantage over Open Wound Treatment in the prevention of SSIs and hence Open wound treatment can be taken as an alternative for occlusive dressings.